Stress buffering effects of leader vision. Issue 20 (12th November 2020) - Newton, Cameron; Bish, Adelle; Anibaldi, Renata; Browning, Vicky; Thomas, Drew
Abstract: Leader vision has been related to a range of favorable outcomes for employees including better job satisfaction and organizational commitment, and lower levels of stress. While direct effects of more distal (organizational level) leader vision have been established, research has yet to explore the effects of different hierarchical levels of leader vision and their potential stress buffering effects on proximal or distal indicators of employee adjustment. Drawing primarily on Conservation of Resources theory and the Job Demand Resources Model, it was predicted that main and stress buffering effects would be significant when the proximal or distal nature of the leader vision (i.e., work unit, departmental, or organizational leader vision) was congruent with proximal or distal employee adjustment outcome types. Two way moderated regression analyses were performed on data collected from a large government organization. The analyses found support for the main effects hypotheses of leader vision on employee adjustment. While stress mitigating effects were observed when there was congruence in terms of the distal leader vision and the distal adjustment outcome types, other significant interactions failed to support hypotheses. Moreover, moderating effects were largely confined to distal leader vision. Theoretical and practical implications are subsequently presented.